Proceedings of the Ocean Drilling Program 1998
DOI: 10.2973/odp.proc.ir.175.118.1998
|View full text |Cite
|
Sign up to set email alerts
|

Lithostratigraphic Summary for Leg 175: Angola-Benguela Upwelling System

Abstract: During Ocean Drilling Program Leg 175, 40 holes were drilled at 13 sites, and 8003 m were recovered with the aim of reconstructing the late Neogene history of the Angola-Benguela upwelling system on the southwest African margin. This system is one of the great upwelling regions of the world and is characterized by organic-rich sediments that provide an excellent record of productivity back to the middle Miocene. Understanding the sedimentology and stratigraphy of these sediments will provide important new info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 6 publications
1
12
0
1
Order By: Relevance
“…The shelf and the slope are deeply incised by a canyon that directly connects the Congo River with the basin floor. Analyses conducted during ODP Leg 175 have shown that turbidity currents played a minimal role in transporting sediment within this part of the Lower Congo Basin (Pufahl et al, 1998;Giraudeau et al, 1998). Coarse sediments trapped into the canyon were carried far onto the lower fan (Savoye et al, 2000;Uenzelmann-Neben, 1998;Jansen et al, 1984a,b) while only muddy sediments are deposited on the slope (Cooper, 1999;Wefer et al, 1998b) and mixed with hemipelagic sediments.…”
Section: Geological Settingsmentioning
confidence: 96%
“…The shelf and the slope are deeply incised by a canyon that directly connects the Congo River with the basin floor. Analyses conducted during ODP Leg 175 have shown that turbidity currents played a minimal role in transporting sediment within this part of the Lower Congo Basin (Pufahl et al, 1998;Giraudeau et al, 1998). Coarse sediments trapped into the canyon were carried far onto the lower fan (Savoye et al, 2000;Uenzelmann-Neben, 1998;Jansen et al, 1984a,b) while only muddy sediments are deposited on the slope (Cooper, 1999;Wefer et al, 1998b) and mixed with hemipelagic sediments.…”
Section: Geological Settingsmentioning
confidence: 96%
“…The majority of the coarser fraction of the Cenozoic post-rift succession is captured by the submarine Congo (Zaire) Canyon ( Fig. 1) (Anka et al, 2009) and hence the Cenozoic succession in the basin is mainly comprised of fine-grained mudstones (Pufahl et al, 1998;Uenzelmann-Neben, 1998). Turbidites and coarsefilled submarine canyons occur occasionally, particularly in the Oligocene and Miocene succession and they often represent excellent reservoirs (Sikkema and Wojcik, 2000;Broucke et al, 2004).…”
Section: The Lower Congo Basinmentioning
confidence: 99%
“…Some sediment is transported off the shelf onto the slope where it is deposited in calcareous nannofossilforaminiferal oozes (Rogers, 1977;Rogers and Bremner, 1991;Pufahl et al 1998). In addition, some terrigenous sediment carried by the Orange River never makes it to the margin, but occurs in palaeoflood deposits along the middle and lower river course, preserved by the high aridity and low vegetation cover in the area (Zawada, 2000).…”
Section: Regional Settingmentioning
confidence: 99%